Waste management through a waste bank based on entrepreneurial readiness in Ngalang Village - Mulasari, Surahma Asti; Tentama, Fatwa; Kusuma, Desta Rizki; Sulistyawati, Sulistyawati; Sukesi, Tri Wahyuni (Intelektual Pustaka Media Utama, 2024)
This research describes entrepreneurial readiness in the waste bank community at Ngalang Village, Gunungkidul Regency. This study is qualitative phenomenological research. This study's respondents were six administrators and members of the waste bank community in Ngalang Village, Gedangsari, Gunungkidul. Respondents were selected using a purposive sampling technique with the characteristics of the respondents: administrators and members of the Ngalang Village waste bank, do not have a permanent job, have an active status, and have been involved for at least one year. The data analysis employed in this research is content analysis. The results of the study show that the entrepreneurial readiness of the waste bank community in Ngalang Village has the skills needed in business, is courageous in dealing with and anticipating business failures, has a social network community that supports business activities, can see business opportunities, and prepare business development plans. In addition, in the waste bank community, they can prepare physically, mentally, and spiritually, have strong personalities, are willing to develop their skills, prepare for business activity, and prepare themselves for marketing the products. This entrepreneurial readiness will eventually become the principal capital in starting a business in the waste bank community.